Places of resistance and memory: reside and resist - Guixé Corominas, Jordi (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The text reflects upon three key axes: the need to consider memory and its physical and symbolic spaces as collective patrimony in our places of residence; the challenge of transmitting and giving new meaning to those spaces as places of resistance and as a patrimony that transforms current and contemporary values; and the most current willingness to carry this out in a way that is transnational, comparative and networked. From there the text addresses a more reflective, conceptual and theoretical element, and another which speaks of the cases studied by way of example of the debates and current conflicts that can be work and analysis models. Concepts such as multiple memory, nostalgic, resistant, uncomfortable, and even conflictive memories are dealt with as concepts, but the author attempts to link them to practical cases through interpretation, cultural and touristic transmission of memory. Methodologically, the text combines theoretical reflection with the practical cases of concrete analysis of spaces of memory.